2017
DOI: 10.3390/en10040561
|View full text |Cite
|
Sign up to set email alerts
|

Methane Hydrate Formation in Marine Sediment from South China Sea with Different Water Saturations

Abstract: Abstract:The kinetics of methane hydrate formation in marine sediments with different water saturations are important to assess the feasibility of the hydrate production and understand the process of the secondary hydrate formation in the gas production from hydrate reservoir. In this paper, the behaviors of methane hydrate formation in marine sediments from the South China Sea at different water saturation levels were experimentally studied in isobaric conditions. The marine sediments used in the experiments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
0
10
0
1
Order By: Relevance
“…Moreover, an increase in the interface area increases the nucleation rate [31]. Therefore, studies of the gas hydrates formation in porous media such as silica gel [32], activated carbon [27,32], corundum, silicon carbide [33], pumice [34], natural marine sediments [35], and clay minerals [36,37] were carried out. However, quartz sand remains the most common medium used for this purpose.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, an increase in the interface area increases the nucleation rate [31]. Therefore, studies of the gas hydrates formation in porous media such as silica gel [32], activated carbon [27,32], corundum, silicon carbide [33], pumice [34], natural marine sediments [35], and clay minerals [36,37] were carried out. However, quartz sand remains the most common medium used for this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…According to studies [43,44], the rate of hydrate formation is higher in quartz sand with smaller particles. Another relevant characteristic for hydrate formation in porous sediments is water saturation [35,40,41,45]. It was shown that an increase in water saturation resulted in a decrease in water to hydrate conversion while the addition of sodium dodecyl sulfate removing this restriction.…”
Section: Introductionmentioning
confidence: 99%
“…The results show that the dissociation area is mainly located around the well, and the gas production is low only through depressurization method [29,30]. Zhang et al investigated the decomposition conditions of methane hydrate and the effect of hydrate saturation on the methane hydrate dissociation, and the results are similar to those of Moridis [32][33][34]. In order to enhance gas production, more and more attention has been paid to the combined method of depressurization and thermal stimulation [35,36].…”
Section: Model Applicationmentioning
confidence: 86%
“…The clay sample from the Shenhu area in the South China Sea was used as the soil skeleton with a grain size ranging from 300 μm to 450 μm . The specific weight of the samples was 2.81 [16]. The dry soil was mixed with deionized water until reaching a water content of 22%.…”
Section: Experimental Apparatusmentioning
confidence: 99%